Meningkatkan Kemampuan Motorik Halus Melalui Kacang Hijau Pada Anak Usia 6 Tahun - Nurbaiti Nurbaiti; Jon Efendi (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2020)
This study aims to improve the fine motoric abilities of six-year-old children at Mardhiyah Bandar Create Kindergarten in Padang. Activities to improve fine motor skills are done by taking green bean seeds and then inserting green bean seeds into bottles. This research was conducted using a single subject research method consisting of two conditions. The two conditions are the baseline condition (A) with five meetings and intervention conditions (B) with seven meetings.Improving fine motor skills by taking green beans from five fingers to two fingers can increase by a percentage of 73% from 25%. It can be concluded that taking green beans with fingers can improve the fine motor skills of a six-year-old child.Based on the results and discussion of children's fine motor abilities can be increased by taking green beans and then put the seeds into a bottle. Therefore, how to take green beans can be applied so that children's motoric development can increase.